Breaking out: the turning point in learning using mobile technology. Issue 3 (March 2021) - Bello-Bravo, Julia; Brooks, Ian; Lutomia, Anne Namatsi; Bohonos, Jeremy; Medendorp, John; Pittendrigh, Barry
Abstract: Despite considerable research on YouTube as a digital media platform, little research to date has quantified the device-type used to access that online media. Analyzing access-device data for videos on one YouTube video channel—Scientific Animations Without Borders (SAWBO), which produces educational content specifically accessible to low- or non-literate, poor, or geographically isolated learners in less developed areas of the world—the results identify the historical moments between 2015 and 2017 when mobile/smartphones, both globally and by region, crossed a tipping point to surpass all other ICT devices (including desktop PCs, laptops, and other Internet-accessing technologies) as the primary device-type for accessing SAWBO videos. Specifically, data from January 2013 to June 2018 obtained for SAWBO's YouTube channel were sampled to capture and distinguish the access device-type used and then summarized in broad global and regional categories. The tipping point, as the date where the percentage of views from mobile phones was equivalent to the percentage of views from computers, were also calculated globally and by region. Besides documenting this critical global-historical moment, the results also have implications for mass digital-messaging generally and mobile-based public service learning specifically. Abstract : YouTube, SAWBO, history of ICT, public service learning.